Association of endothelial nitric oxide synthase intron 4a/b gene polymorphisms and hypertension: a systematic review and meta-analysis - Xiru Xu (SAGE Publishing, 2021)
Objective We conducted meta-analysis of relevant case-control trials to determine the association between endothelial nitric oxide synthase (eNOS) intron 4a/b gene polymorphisms and hypertension susceptibility. Methods We searched the PubMed, Cochrane, and Embase databases using relevant keywords and reviewed pertinent literature sources. All articles published up to July 2019 were considered for inclusion. Based on the qualified studies, we performed a meta-analysis of the associations between eNOS intron 4a/b polymorphisms and the risk of hypertension. Results Fourteen studies were included in this meta-analysis, including 3344 cases and 3377 controls. The eNOS intron 4a/b locus was significantly associated with increased susceptibility to hypertension (including essential hypertension) in the overall population, according to dominant, allelic, homozygote, heterozygote, and regressive models, in the mixed population according to the regressive model, and in Caucasians according to the dominant, allelic, heterozygote, and regressive models. The eNOS intron 4a/b locus was also significantly associated with increased susceptibility to essential hypertension in the mixed population according to the heterozygote model. Conclusion eNOS intron 4a/b gene polymorphisms increase susceptibility to hypertension, including essential hypertension.